2019
DOI: 10.1063/1.5054703
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of silicon surface states by Al-induced acceptor states from Al–O monolayers in SiO2

Abstract: Realization of rhombohedral, mixed, and tetragonal like phases of BiFeO 3 and ferroelectric domain engineering using a strain tuning layer on LaAlO 3 (001) substrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…14 The Al-induced acceptor states have also been shown to reduce the electrically active D it at the Si/SiO 2 interface, attributed to an interface defect deactivation mechanism that involves the discharge of the singly occupied dangling bonds (P b0 defects) into the acceptor states, without any need for passivation with H 2 . 15 The SiO 2 layer is thus required for the negative Q fix in Al 2 O 3 , and the thickness, oxygen content, impurities, and structure of this layer should affect the surface passivation properties. Indeed, it has previously been demonstrated that thermally grown SiO 2 has a significantly reduced positive field-effect passivation compared to deposited SiO 2.…”
Section: Introductionmentioning
confidence: 99%
“…14 The Al-induced acceptor states have also been shown to reduce the electrically active D it at the Si/SiO 2 interface, attributed to an interface defect deactivation mechanism that involves the discharge of the singly occupied dangling bonds (P b0 defects) into the acceptor states, without any need for passivation with H 2 . 15 The SiO 2 layer is thus required for the negative Q fix in Al 2 O 3 , and the thickness, oxygen content, impurities, and structure of this layer should affect the surface passivation properties. Indeed, it has previously been demonstrated that thermally grown SiO 2 has a significantly reduced positive field-effect passivation compared to deposited SiO 2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to passivating contacts, Si-SiO2 has been reported to be vital for aluminium oxide passivation of p-type surfaces [7][8][9]. An interfacial SiO2 is required for the alumina layer to build substantial negative charge [10], and in some cases it has been used to control the total negative charge concentration [11,12]. This negative charge in AlOx passivation layers have made them key in minimising surface losses on p-type Si at the cell's rear, and have thus enabled the ongoing industrial shift to Passivated Emitter and Rear Cell (PERC) technology [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[43] Secondary ion mass spectrometry of an annealed ALD Al 2 O 3 lm deposited on H-terminated Si has also previously shown that at the depth where1/3 of the detected atoms are Si, which would be expected from tetrahedrally coordinated Si in SiO 2 , 1/5 of the detected atoms are Al, thus revealing large amounts of Al in the SiO x layer. [44] As the xed negative charge of Al 2 O 3 is primarily attributed to an oxygen rich layer with O interstitials and Al vacancies with tetrahedrally coordinated Al that is prevalent partly due to the tetrahedrally coordinated Si in SiO x , [11][12] it is not surprising if large amounts of Al in the SiO x layer may have a detrimental effect, and thus can explain the slightly reduced negative Q x observed in HF-dipped samples relative to no-HF samples. Al impurities are also associated with increased D it .…”
Section: Discussionmentioning
confidence: 99%
“…[11] Hiller et al have also demonstrated that electrically active surface states of silicon can be deactivated by Al-induced acceptor states in SiO 2 in a similar manner. [12][13] The xed charges created in this way will be compensated by an equal positive charge in the silicon, and do not directly repel charges away from the interface, however, the number of trapped electrons in the SiO x -Al 2 O 3 interface layer is large, with Q x > 10 12 cm − 2 , [3,[14][15][16] implying that the number of electrons near the surface region of silicon is signi cantly reduced, thereby sharply reducing the probability of electron-hole recombination in the same way as a p + layer in p-type Si does. [17] Annealing at > 400 ˚C in N 2 , forming gas (FG), or O 2 , reduces D it from > 10 12 ev 1 cm 2 to < 10 11 ev 1 cm 2 , [3,[14][15][16] commonly attributed to either hydrogen diffusion towards the Si-SiO x interface passivating the Si dangling bonds near the surface and in the bulk, or by increased SiO x formation between Si and Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%